0480 Efficacy and Safety of Lemborexant in Female Subjects of Perimenopausal Age with Insomnia Disorder. (27th May 2020) - Cheng, J; Yardley, J; Pinner, K; Moline, M
Abstract: Introduction: Insomnia is common in women in the perimenopausal age range. We present 12-month efficacy and safety data for the subgroup of female subjects in the age range associated with perimenopause (age 40-58y) from SUNRISE-2 (NCT02952820; E2006-G000-303). Methods: SUNRISE-2 was a 12-month, randomized, double-blind, placebo (PBO)-controlled (first 6mo [Period 1]), global phase 3 study. During Period 1, subjects received PBO or lemborexant (LEM: 5mg, [LEM5]; 10mg, [LEM10]). During Period 2 (second 6mo), LEM subjects continued their assigned dose. PBO subjects were rerandomized to LEM5 or LEM10 (not reported here). Changes from baseline in subjective sleep parameters: subjective sleep onset latency (sSOL), sleep efficiency (sSE), wake after sleep onset (sWASO) were assessed from sleep diary data. Results: The perimenopausal subgroup comprised 280 subjects (Period 1: PBO, n=90; LEM5, n=82; LEM10, n=108). Baseline median sSOL (min) was 57.5, 51.1, and 54.0 for PBO, LEM5, and LEM10. Greater median decreases from baseline in sSOL (min) occurred at 6mo with LEM vs PBO (PBO, −17.9; LEM5, −20.7; LEM10, −30.4); improvements persisted at 12mo (LEM 5, −27.7; LEM10, −33.9). Baseline mean[SD] sSE was 59.9%[16.6%], 60.7%[20.0%], and 61.2%[17.5%] for PBO, LEM5, and LEM10. Greater mean[SD] increases from baseline in sSE (%) occurred at 6mo with LEM vs PBO (PBO, 12.5%[15.0%]; LEM5, 15.9%[17.0%]; LEM10, 17.2%[14.7%]); improvement persisted at 12mo (LEM5, 17.6%[18.2%]; LEM10, 19.1%[14.8%]). Baseline mean[SD] sWASO (min) was 134.9[70.8], 142.4[86.5], and 136.5[84.4]. Greater mean[SD] decreases from baseline in sWASO (min) occurred at 6mo with LEM vs PBO (PBO, −37.0[59.6]; LEM5, −50.1[74.5]; LEM10 −54.5[65.4]); improvement persisted at 12mo (LEM5, −59.1[76.7]; LEM10, −66.2[64.9]). Most treatment emergent adverse events (TEAEs) were mild/moderate. Conclusion: Consistent with previously reported data from the total population, subjective sleep parameters improved, and improvement was sustained over time in perimenopausal women. LEM was well tolerated, supporting LEM as a potential treatment option for perimenopausal women with insomnia. Support: Eisai Inc.